The last hope of survival: Hemisection of mandibular molar - Sushmita Esh; H D Adhikari (Wolters Kluwer Medknow Publications, 2022)
Hemisection denotes a procedure which saves the multi-rooted teeth by endodontic approach of the restorable half and deliberate excision of the compromised tooth structure, as opposed to extraction, that sacrifices the whole tooth. In the present case report, conventional root canal therapy of the root, to be saved, was performed, followed by hemisection of the affected root with the vertical cut method. When complete healing at the surgical site was observed, clinically and radiographically, fixed dental prosthesis was given. Radiographic success observed at recall visit indicated bone formation at the extraction site and the tooth was found to serve normal function. It was a conservative approach aiming to retain as much original tooth structure as possible against the option of extraction of the natural tooth.